Sections 135 and 136: Running a health-based place of safety in Gloucestershire. (April 2016) - Pugh, David; Laidlaw, Jim
The Maxwell Centre, a health-based place of safety (POS) adjacent to a psychiatric hospital, was opened in Gloucestershire in February 2009. It provides a POS for people detained under Sections 135 and 136 of the Mental Health Act 1983 as amended in 2007. Prior to the opening of the Maxwell Centre, police cells were the only designated POSs. To assess the impact of the opening of this new facility, we undertook a service evaluation. In the five years (February 2009 to December 2013) following the opening of the Maxwell Centre, the use of Section 136 increased by more than 60%.